IRF6 Regulates Alternative Activation by Suppressing PPARγ in Male Murine Macrophages - Li, Chuan (Endocrinology, 2017)
Aberrant proinflammatory and suppressed anti-inflammatory (alternative; M2) macrophage activation underlies the chronic inflammation associated with obesity and other metabolic disorders. This study demonstrates a critical role for interferon regulatory factor 6 (IRF6) in regulating macrophage M2 activation by suppressing peroxisome proliferator–activated receptor-γ (PPARγ) expression, a critical regulator of alternative macrophage polarization. The data demonstrate suppression of IRF6 in both M2 macrophages and obese adipose tissue macrophages. Using gain- and loss-of-function strategies, we confirmed that IRF6 knockdown enhanced M2 activation, whereas IRF6 overexpression dramatically attenuated M2 activation. Computational target prediction analysis coupled with chromatin immunoprecipitation indicated that IRF6 suppresses PPARγ through binding IRF recognition sites located upstream of the PPARγ coding region. Taken together, our results suggest that an IRF6/PPARγ regulatory axis suppresses anti-inflammatory responses in bone marrow–derived macrophages and provides references for future study addressing dysregulated metabolic and immunologic homeostasis of obese adipose tissue.